Habits, Quick and Easy: Perceived Complexity Moderates the Associations of Contextual Stability and Rewards With Behavioral Automaticity - McCloskey, Kiran; Johnson, Blair T. (Frontiers in Psychology, 2019)
Background: Habits have been proposed to develop as a function of the extent to which a behavior is rewarded, preformed frequently, and executed in a stable context. The present study examines how each of these factors are associated with behavioral automaticity across a broad variety of behaviors drawn from previous habits research. This study further assesses how perceived complexity of the behavior influences the associations of rewards, frequency, and contextual stability with automaticity. Method: Participants (N = 459) completed an online survey assessing their experiences and engagement with 25 different behaviors, including exercise, handwashing, smoking, and medication adherence. Exploratory factor analysis validated a short, relatively novel scale of perceived behavioral complexity, and multilevel analyses grouped by participant were used to examine the factors that contribute to automaticity. Results: Across behaviors, frequency, contextual stability, and perceived rewards were positively associated with automaticity. Perceived complexity was negatively associated with automaticity and moderated the influence of contextual stability and rewards, but not frequency, on automaticity. Both contextual stability and rewards were stronger predictors of automaticity when behavioral complexity was high rather than low, as predicted; in addition, when contextual stability was high, more complex behaviors showed greater automaticity than simpler behaviors. Conclusions: The results of this study confirm that behavioral frequency, rewards, and contextual stability are each independently associated with automaticity across a spectrum of behaviors. This study further demonstrates that perceived complexity of a behavior moderates the extent to which contextual stability and rewards are associated with automaticity. The results affirm a need to further understand the components of habits and how they differ across varying behaviors.